PENGEMBANGAN MEDIA PEMBELAJARAN "RUMAH PINTAR" UNTUK ANAK USIA 4-5 TAHUN DI TK AL AZHAR 21 PONTIANAK - Yuniarni, Desni (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
The purpose of this research is the development of learning media for children aged 4-5 years in Islamic Kindergarten Al Azhar 21 Pontianak named "Rumah Pintar". The existence of this learning media is expected to be a useful reference for PAUD science and contribute to learning in PAUD, especially at Al Azhar 21 Islamic Kindergarten in Pontianak. In order to fulfill the research objectives, the researcher uses a 4D development model, namely define, design, develop, and disseminate which can be adapted into 4Ps, namely definition, design, development, and dissemination. The research subjects were teachers at Al Azhar 21 Islamic Kindergarten in Pontianak. Sources of research data are PAUD practitioners with a Masters in PAUD education and involve psychologists who work in PAUD Pontianak city to obtain validation data from material experts and PAUD media experts. The method used is the method of interviews and questionnaires. The data analysis technique used in this research is descriptive qualitative and quantitative analysis techniques. The results of the study show that the "Smart House" learning media is suitable for children aged 4-5 years after being revised from input from research subjects and validators of material experts and media experts.